Strategic Analysis Of The Investment Position Of South Africa On The Foreign Investment Market - Belyak, Alexey Vladimirovich; Matraeva, Liliia Valerievna (Advances in Social Sciences Research Journal, 2017)
This article is devoted to the investment attractiveness of the country. The authors would like to propose their own approach, using South Africa as an example. The authors demonstrate the way to analyze the investment position of the country and work out recommendations for the future development, given ready available statistical data. This method can be applied to any other country as it is based on Global Competitiveness Report covering all the countries in the world as well as UNCTAD and IMF data. Based on this data authors have prepared SWOT analysis with detailed review of strengths, weaknesses, opportunities and threats which is based on statistical data rather than on expert opinions. The analysis covers the years 2010 and 2014. The year 2010 was chosen as the first year after crisis. The year 2014 was taken because for the year 2015 there was no data regarding the level of FDI which is crucial for defining investment position. Therefore year 2014 contains the most recent data about FDI. The conducted analysis resulted in the statement that considering all the analyzed features and development factors of the country, the current position on the investment map, strengths and weaknesses, threats and opportunities, South Africa should make a choice of a strategy between the strategies for accelerated growth and limited growth in favor of the latter.